(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The park of metal cylindrical tanks in Ukraine is characterized by significant wear of load-bearing structures, corrosion of elements and metal fatigue of vertical connections. One of the solutions to the replenishment of the lost load-bearing capacity of their walls is the reinforcement by external transverse FRP. It is also make it possible to ensure tightness and anti-corrosion protection of these constructions. At the same time, existing recommendations assessing the effective use of various types of FRP, differing in strength, deformation and thermal deformation parameters, are insufficient in relation to the strengthening of metal cylindrical shells. This work systematizes systematize the method of practical determination of the parameters of the stressed state of elements of metal cylindrical shells reinforced with external transversely directed FRP reinforcement and detecting the main factors influencing the effectiveness of the use of FRP based on fibers of various types in combination with steels of different strengths. The analysis of the given theoretical dependencies allows to conclude that the mandatory factors to be taken into account for strengthening of the metal cylindrical shells by external transversely directed FRP reinforcement that perceives the actions of ring forces are the temperature deformations of used FRP materials, as well as the longitudinal deformations of the metal components of complex walls. The main factors determining the effectiveness of the obtained solutions are the residual strength of the material of the metal shells and the modulus of elasticity of the used FRP. The influence of thermal deformations can repeatedly change the required degree of external reinforcement of structures in the case of the using FRP based on various types of structural fibers in combination with steel shells that characterized by low material strength, while similar combinations with high-strength steels can neutralize the influence of temperatures. The effective use of low-modulus FRP can be achieved for reinforcements of the structures with high strength characteristics of steel. For the structures characterized by low steel strength effective external reinforcement is achieved in combination with high-modulus FRP. The influence of temperature deformations leads to that the FRP reinforcements made on the basis of aramid fibers demonstrate relative ineffectiveness in combination with shells characterized by low steel strength.